Proposta de um sistema fotovoltaico residencial conectado à rede - LAGO, Larisse Mendes (2019)
Interest in renewable energy has grown considerably in recent years due to concern for the environment and to seek an alternative to fossil fuels along with the need to expand the availability of electricity to meet the demand for energy. This work presents initially a general approach and examples of renewable and alternative energy sources, emphasizing the solar energy and its photovoltaic energy applications that are quite diversified, being able to be used as a source of isolated communities or in applications connected to the network. This study considers the sizing project of a Photovoltaic Solar System Connected to the Network and isolated, installed in the residence of the student, located in the district Jardim Paraíso, municipality of Tucuruí, state of Pará. The work shows a detailed analysis of the house installations and the type of load installed in each of the environments. From this, an estimate of the monthly consumption of the building is carried out, so that the systems can be compared with that of the energy distribution company.